PENGARUH MOTIVASI KERJA TERHADAP KINERJA GURU PADA SMK NEGERI 1 BELITANG III KABUPATEN OGAN KOMERING ULU TIMUR - Ika Lestari, Wahyu (Jurnal Trisna Riset, 2023)
Teachers are the front guard in the world of education and one of the components that occupies a central and very strategic position in the education system, where teachers at SMK Negeri 1 Belitang III are required to carry out their duties, requiring strong and high teacher enthusiasm and work motivation in order to achieve the goals that have been set. The importance of motivation is because motivation is what causes, channels and supports human behavior, so that they are willing to work hard and enthusiastically achieve optimal results. to be done well and integrated to the desired goals. The problem faced by SMK Negeri 1 Belitang III East Ogan Komering Ulu Regency is "How does work motivation influence teacher performance at SMK Negeri 1 Belitang III East Ogan Komering Ulu Regency". The hypothesis proposed is that motivation has a strong influence on teacher performance at SMK Negeri 1 Beliatang III, East Ogan Komering Ulu district. The data collection techniques used were observation, questionnaires, documentation and literature study. From the calculation results, the figure r = 0.73 was obtained, it turns out that 0.73 is located between 0.61 - 0.80 which is included in the strong correlation. Then to answer the hypothesis test proposed in the previous chapter and get to = 3.021. The conclusion from this research is that there is a strong influence between motivation and teacher performance. Suggestions from the research are the need for high awareness from the teachers themselves to act as effectively and maximally as possible in carrying out their work without having to be motivated first.